The effect of genistein on cisplatin induced ototoxicity and oxidative stress - Tan,Mehmet (2022)
Abstract Highlights Cisplatin is an antineoplastic agent used malignant diseases. Cisplatin ototoxicity is generally bilateral, irreversible, and progressive. Genistein is a phytoestrogen. Genistein functions as antioxidant and cell cycle inhibitor by inhibiting DNA topoisomerase. Genistein showed positive effects on ototoxicity with its antioxidant. Objective Cisplatin is an antineoplastic agent used in adults and children for the treatment of various malignant diseases. It can cause irreversible ototoxicity. Genistein is a phytoestrogen. Genistein functions as an antioxidant and cell cycle inhibitor by inhibiting the DNA topoisomerase and tyrosine protein kinase enzymes. The protective effect of genistein in preventing cisplatin-induced ototoxicity and levels of the oxidative stress was investigated. Methods 32 Sprague Dawley rats were used in 4 groups (control, cisplatin, cisplatin + genistein, genistein). Otoacoustic emission measurements of the distortion product were performed on the 1st, 2nd and 5th days of the test protocol. Serum malondialdehyde, superoxide dismutase, catalase, glutathione peroxidase, total antioxidant status, total oxidant status and oxidative stress index measurements were made. Results The hearing of the cisplatin + genistein group was found to be better than that of the cisplatin group. While the malondialdehyde, total oxidant status and oxidative stress index parameters decreased significantly in the cisplatin + genistein group compared to the cisplatin group, superoxide dismutase increased significantly (p < 0.05). Conclusion Genistein showed positive effects against ototoxicity with its antioxidant effect. Level of evidence Level 3.